Psychological strain between nurses - Andrea Obročníková; Dagmar Magurová; Ľudmila Majerníková; Mária Kaščáková; Mária Harčariková (University of Ostrava, 2015)
Aim: The aim of the study was to identify differences in perception of work (mental) workload among nurses providing acute and chronic nursing care. Design: Study design is cross-sectional and descriptive. Methods: The sample of respondents consisted of 97 nurses working in departments Neurology, Anesthesiology and Intensive Care Unit of the hospital St. James in Bardejov, University Hospital of L. Pasteur in Košice and University Hospital J. A. Reiman in Prešov. To measure psychological strain, Meister's questionnaire for neuropsychological strain was used. Results: Increased psychological strain was observed in nurses providing acute care versus nurses providing chronic care, particularly in job satisfaction, long-term tolerance, time constraints, high responsibility, nervousness, fatigue and satiety. In comparison with the population norm, nurses in acute care achieved significantly higher indicators of factor I (strain) and gross score as nurses in neurological care. A statistically significant relationship between psychological stress and age of nurses working in anesthesiology and intensive care departments was confirmed. Nurses with long term practical experience are exposed to intense mental stress (especially in the areas of strain and monotony). Conclusion: The results of our study suggest the reality that variable qualities of work related strain among nurses can lead to physical and emotional exhaustion.